You Can't Teach a Kid to Ride a Bike at a Seminar - Sandler, David H. (Ascent Audio, 2017)
The timeless guide to sales success has been revised to help you supercharge personal and team performance in a new economy. "People make buying decisions emotionally and justify them logically." That shrewd insight from the first edition of this best-selling book has become a no-brainer among sales professionals. Now, the new edition of the classic work that has helped millions of sales professionals take their careers to new levels offers critical new insights, information, and tools for success in today's economy. You Can't Teach a Kid to Ride a Bike at a Seminar, Second Edition retains David Sandler's classic, battle-tested advice on driving personal and organizational success by breaking the rules of conventional selling. And now Sandler Training's CEO, David Mattson, has revisited it to provide additional skills designed for today's highly competitive and more complex sales landscape. With this powerful guide, you'll learn how to: - Take the lead in the "buyer/seller dance" - Get the prospect to do most of the talking - Have a process for answering questions from prospects - Know when a prospect is shopping you . . . and what to do about it.